Development of a computer program for determining the freight charge in the conditions of KARAGANDA TRANS-COAL LLP - Balabaev O.T. Балабаев О.Т.; Akhmetsadyk O.E. Ахметсадык О.Е.; Rakhimov A.B. Рахимов А.Б.; Naviykhan B Навийхан Б (Рroblems of engineering and professional education, 2023)
The article deals with the results of the analysis of the products of the programs used to determine the toll payment in railway transport. A computer program has been developed that is used to determine the fee payment under the terms of "Karagandy trans-coal" LLP. The performed work expands the use of serious computer technology in railway transport.